Computer simulation of abnormal glow discharge processes in crossed electric and magnetic fields - Isakov, A.V.; Kolesnik, V.P.; Okhrimovskyy, A.M.; Stepanushkin, N.P.; Taran, A.A. (Вопросы атомной науки и техники, 2014)
A mathematical model for plasma parameters calculation in the abnormal glow discharge in crossed electric and magnetic fields is proposed. Numerical model made it possible to obtain the electric potential, electric field, electron density and temperature distributions in the interelectrode space working area. The application validating of the developed numerical model has proved to describe of the processes in the magnetron-type devices.